Developing Formula to Calculate Compensation for Overseas Employee - Auzini, Dea Monica (Journal of Business and Management, 2012)
Human Resource Management is one important thing to be considered in an organization, especially when related to the Remuneration System or Employee’s Compensation System. Because the compensation system is directly related to employee’s performance and employee’s satisfaction that will impact the increasing or decreasing of the company's performance. As the company prepared to become a world-class company, PT X has conducted many partnership activities with foreign company. But, there are several problems that arise related to the employees who are assigned outside the country. One them is about the compensation system and the amount of salary that the employee received. Some employees who are assigned to work abroad felt dissatisfied with the compensation system and the salary they receive from the partnership company. However, complaints from the employees cannot be handled by company because of the absence of salary calculation formula or calculation system for employees working abroad. In order to solve that problem, the company needs a formula or a salary calculation system to determining salaries for employees who are assigned overseas company. The calculation system should consider the risks such as cost of living allowance, hardship allowance, transportation allowances, housing allowances, and educational assistance that will be faced by the employees and compensate those risks. This salary calculation system is expected to be a reference for companies to calculate the minimum salary received by an employee. Keywords : salary, overseas employee, compensation system, compensation formula, overseas employee compensation